Pengembangan Lembar Kerja Mahasiswa Berbasis Project Based Learning Pada Kuliah Analisis Makanan dan Obat Program Studi Analis Kimia - Nelson Nelson; Indra Lasmana Tarigan (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Science process skills are basic skills needed by students to form problem solving abilities. The purpose of this research is to produce Student Worksheet based on project-based learning to train science process skills in the Food and Drug Analysis course which is theoretically feasible based on validation results and feasible based on implementation and student responses. This research includes development research using the 4D method, which consists of define, design, develop, and disseminate. In the disseminate stage, a student worksheet trial was conducted on student participants in the Chemical Analyst D3 Study Program, Faculty of Science and Technology, Jambi University. Data collection using validation and observation methods. The results of the study indicate that project-based learning-based MFIs can train students' science process skills with a validity value of 73.30 with appropriate criteria. The use of student worksheet with a project-based learning approach can improve student problem solving in the food and drug analysis course. The increase in problem solving is in the medium category.